Some heavy Metal pollution investigation in Sulaimani province groundwater - Ahmad, Ali Bawasheakh; Esmail, Akram O. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The paper aims to go into the impact of some heavy metal contamination in the Sulaimani province groundwater for irrigation purpose. Water samples were collected from (36) locations in the study area that not the same and the heavy metals such as (Iron, Zinc, Copper and Manganese) were finding out by using Atomic Absorption Spectrophotometer. Heavy metal contamination appraisal in ground water required cognition of pre anthropogenic metal concentrations to act as a reference against which measured values can be compared. Groundwater taint by heavy metal was accomplished using Enrichment Factor (EF), Metal Contamination Index (MCI), Contamination Factor (CF), Pollution Index (PI), Contamination degree (Cd), modified Contamination Degree (mCd), Pollution load Index (PLI) and Index of geo accumulation (Igeo). Established on the above exponents, the results indicate the study groundwater resources to be very low degree of contamination.
Keywords: Trace elements; Heavy metals; Anthropogenic; Contamination; Enrichment Factor EF; Contamination Factor CF; Contamination degree Cd; Pollution load Index PLI and Geo accumulation Index Igeo